An objectivist-constructivist blended approach: implications on student achievement and satisfaction in Malaysian university-level beginner string technique classes / Shafizan Sabri - Sabri, Shafizan (2016)
This study explores the impact of blended-approach teaching on students' achievement and satisfaction in a Malaysian university-level beginner string classes. Specifically, this study incorporated a blended objectivist-constructionist approach, together with Dick and Carey's (Dick, Carey and Carey, 2005) instructional design system, to create instructional materials for beginner string technique class. Researchers in general concur that the objectivist and constructivist approaches positively affect the teaching and learning process in the music classroom. Specifically, the constructivist teaching strategy of modeling, communication, exploration, and experimentation has been proven effectual in enhancing students' achievement and potential. Hence, these teaching strategies were incorporated into the blended approach to put together innovative instructional materials for teaching beginner string ensembles. This research used a non-equivalent control group post-test under a quasi-experimental design. The sample of the study consisted of 40 music students from two public universities in Malaysia. None of the students had had any prior instrumental music training. The students were purposively allocated to one of the two instructional material; these were (a) an experimental group that were subject to the blended approach, using instructional materials based on Dick and Carey (Dick, Carey and Carey, 2005) ;and (b) a control group that received conventional teaching via instructional materials based on printed method books. Following the 14-week treatment, the students completed an achievement test, performance assessment, and satisfaction survey. The achievement test was constructed to evaluate the students' cognitive aspects. Meanwhile, the performance assessments were psychomotor tasks designed to evaluate what the students were able to do. The satisfaction survey provided feedback from each student on the effectiveness of both instructional materials. The results revealed that blended-approach instructional material had a positive impact on students' achievement, as shown by the achievement test. A Mann- Whitney U test revealed a significant difference between the two groups, with the experimental group demonstrating superior achievement compared to the control group (U= 124.5, p = .04). Statistical analysis conducted on group mean scores in the total score for the performance assessments showed that the blended approach teaching material group scored highest. A t-test revealed this difference not to be statistically significant (t = .971, p = .338). However, statistical analysis conducted on the total ordinal score of the student satisfaction surveys revealed that the conventional teaching group scored higher in terms of total ordinal score. This difference was found not to be statistically significant via a Mann-Whitney U test (U = 153.0, p = .203). The results of this study suggest that both instructional materials, blended-approach teaching material, and conventional teaching materials have comparable effects on students' achievement and music performance skills. Given that teaching music is a multidimensional process, several approaches ought to be implemented together in order to provide the most appropriate environment for learning. A combination of blended-approach and conventional teaching materials may create a plethora effect in teaching university-level beginner string technique classes.